Fungi isolated from wild birds in the Marambaia Island, Rio de Janeiro State, southeastern Brazil - Jhon Lennon Genovez-Oliveira; Lucas A.S. Andrade; Mariana S. Oliveira; Viviane M. Lima; Bruno P. Berto; Águida A. de Oliveira (Pesquisa Veterinária Brasileira, 2024)
ABSTRACT: In Brazil, the Atlantic Forest has been suffering from deforestation, which has had impacts on its flora, fauna, and microbiota. However, the fungal diversity present in these environments is little known and studied. In this study, a total of 90 samples of 45 wild birds (45 feathers and 45 feces) were collected in Ilha da Marambaia, southeastern Brazil. Filamentous fungi isolated from these samples were identified through macroscopic and microscopic characteristics. Some isolates were identified by molecular biology using the PCR technique. Acremonium, Alternaria, Aspergillus, Cunninghamella, Curvularia, Eurotium, Fusarium, Geotrichum, Neosartorya, Pestalotia, Paecilomyces, Penicillium, Rhizopus, Mucor and Syncephalastrum were identified. These results indicate the presence of saprophytic fungi species in the feathers and feces of wild birds of the capture site. Further studies should be conducted to elucidate if the mycobiota profile modifies with anthropization and if it interferes with bird health and environmental recovery.